Analisis Pemilihan Lokasi untuk Kepentingan Umum Kabupaten Pringsewu - Zulqadri Ansar (Journal of Science and Applicative Technology, 2021)
Land development that occurs in Pringsewu Regency is for the public interest, as a government step to more easily acquire lands which function as cultivation areas for physical development as a form of service to community needs. The limited provision of land will make it difficult for the government to develop an area as a form of land use for public purposes. This research will discuss about the analysis of land use for the public interest. There are several criteria and indicators that determine the location of land to be used for public use, consisting of land area, existing land use, spatial plan, area function, slope, land shape, soil movement, flood hazard, population density and market land prices. Based on the results of the scoring analysis of 11 indicators through the application of spatial multicriteria analysis which involves eleven criteria for determining the location as the most appropriate variable to be used as state land as a balancing material, the Pringsewu Regency government explains that zone 3 (Kecamatan Pagelaran, Pringsewu dan Ambarawa) has the most land dominance which can be prioritized first.